The encyclopedia of inventions - Sachs, Jessica Snyder (New York : Franklin Watts, 2001)
Describes over 200 inventions in their historical context.
Includes index.
6.8.
6.8
5-8
Keywords: Inventions -- History -- Encyclopedias, Juvenile; Inventions -- History -- Encyclopedias; Inventions -- History -- Encyclopedias